Pengaruh Promosi Serta Pelayanan Secara Online Melalui Whatsapp Terhadap Penjualan Pada “Izhani Olshop” - Rico Septia B.; Nurhasan Nurhasan (FEB Universitas Maritim Semarang, 2023)
In an era full of technological developments, various daily activities are connected with the help of the internet, making operations easier and faster. One use of this technology, for example, is massive marketing activities carried out via social media, one of which is WhatsApp. This application introduces WhatsApp Business features specifically designed to facilitate the marketing of their products to consumers. This increase in the number of WhatsApp users opens up more opportunities for businesses to maximize the application's potential as a digital marketing tool. The aim of this research is to determine the effect of promotions and services via WhatsApp on sales. This type of research is quantitative research. The sample used in this research was 37 people using the questionnaire distribution method as a data collection tool. The analysis technique used in this research is multiple linear regression analysis using the SPSS software application. The research results show that variable X1 (promotion) and variable X2 (service) each influence variable Y (sales) in a positive direction. Besides that, variables X1 (Promotion) and X2 (Service) in the model together are able to explain 40.3% of the influence on variable Y (Sales).